Description of a male of the Peruvian tarantula Thrixopelma aymara (Chamberlin, 1916), and a new species of Thrixopelma Schmidt, 1994 from Peru (Araneae: Theraphosidae: Theraphosinae), with comments on the conservation of tarantulas in Peru - Kaderka, Radan (2025)
The male of the Peruvian tarantula Thrixopelma aymara (Chamberlin, 1916) coming from the type locality is described, re-diagnosed and illustrated. A new species of Thrixopelma Schmidt, 1994, Thrixopelma zaratensis sp. nov. from the Department of Lima in Peru, is herein described, diagnosed and illustrated. Additionally, we discuss the conservation of tarantula species in Peru.